2021
DOI: 10.12659/ajcr.929883
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrasound-Guided Sialendoscopy with Holmium: Yttrium Aluminum Garnet (YAG) Laser Treatment of Parotid Sialolithiasis

Abstract: Patient: Male, 38-year-old Final Diagnosis: Parotid sialolithiasis Symptoms: Painful • swelling Medication: — Clinical Procedure: — Specialty: Surgery Objective: Unusual setting of medical care Background: At present, promptly diagnosing sialolithiasis is easy with the assistance of various noninvasive diagnostic procedures. However, the treatment of parotid sialolithiasis rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Recent publications have reported that simultaneous application of ultrasound and sialendoscopy can further improve the treatment options in difficult situations [ 111 , 112 ]. When the various treatment modalities are considered, a declining trend in the indications for ESWL is evident, particularly in stones located up to the proximal duct.…”
Section: Updated Treatment Algorithm For Parotid Gland Stonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent publications have reported that simultaneous application of ultrasound and sialendoscopy can further improve the treatment options in difficult situations [ 111 , 112 ]. When the various treatment modalities are considered, a declining trend in the indications for ESWL is evident, particularly in stones located up to the proximal duct.…”
Section: Updated Treatment Algorithm For Parotid Gland Stonesmentioning
confidence: 99%
“…Simultaneous application of ultrasound and sialendoscopy has been reported to further improve the treatment options in selected cases, particularly in parotid sialolithiasis [ 111 , 112 ]. US-guided stone extraction alone, without sialendoscopy, has been described [ 113 ], but appears to play only a minor role, if any, if sialendoscopy is not available.…”
Section: Introductionmentioning
confidence: 99%